Evaluating Fitts' law on vibrating touch-screen to improve visual data accessibility for blind users. Issue 112 (April 2018) - Lahib, Manahel El; Tekli, Joe; Issa, Youssef Bou
Highlights: Reviews the literature on Fitts' Law and visual data accessibility solutions for blind users. Studies the ability of blind users to point to shapes on a vibrating touch-screen (VTS). Varies different pointing task parameters: target distance, target size, and angle of attack. Fitts' Law can be applied for blind users using a VTS when varying target distance and target size. Fitts' Law is not verified for blind users using a VTS when varying the angle of attack. Abstract: The pointing task is the process of pointing to an object on a computer monitor using a pointing device, or physically touching an object with the hand or finger. It is an important element for users when manipulating visual computer interfaces such as traditional screens and touch-screens. In this context, Fitts' Law remains one of the central studies that have mathematically modeled the pointing method, and was found to be a good predictor of the average time needed to perform a pointing task. Yet, in our modern computerized society, accessing visual information becomes a central need for all kinds of users, namely users who are blind or visually impaired. Hence, the goal of our study is to evaluate whether Fitts' Law can be applied for blind candidates using the vibration modality on a touch-screen. To achieve this, we first review the literature on Fitts' Law and visual data accessibility solutions for blind users. Then, we introduce an experimental framework titled FittsEVAL studying the ability of blind users to tap specific shapes on a touch-screen, while varying different parameters, namely: target distance, target size, and the angle of attack of the pointing task. Experiments on blindfolded and blind candidates show that Fitts' Law can be effectively applied for blind users using a vibrating touch-screen under certain parameters (i.e., when varying target distance and size), while it is not verified under others (i.e., when varying the angle of attack). This can be considered as a first step toward a more complete experimental evaluation of vibrating touch-screen accessibility, toward designing more adapted interfaces for the blind.